Application Of Neo Vernacular Architecture In Tongging Agrotourism Planning - Lindarto , D.; P, Joel (Jurnal Koridor, 2019)
Tongging is a village in the Lake Toba region that located in the District of Merek, Karo Regency. Tongging Village is famous for its panoramic beauty and the local potential of agriculture and fisheries. With various potentials owned by Tongging Village, a place is needed that can accommodate this potential. Tongging Agrotourism is a place to carry local potential in Tongging Village. Agrotourism is designed to attract more tourists while developing the local potential in Tongging Village. Design with Neo Vernacular Architecture approach to re-apply local cultural elements to optimize their potential. The neo vernacular architectural approach process uses transformation and modifications methods to the physical and non-physical aspects. The architectural aspect adopted as neo vernacular approach is the Karo settlement pattern, circulation, mass, and space program. Tongging Agrotourism has various facilities that support tourism activities at Tongging Village, including rice fields and fish cages, main buildings, cottages, restaurants, processing plants, and research and development areas.